Inhibition of mevalonate 5-diphosphate decarboxylase by fluorinated substrate analogs - Qiu, Yongge; Li, Ding (Biochimica et biophysica acta, 2006)
Mevalonate 5-diphosphate decarboxylase (MDD) is a peroxisomal enzyme in the cholesterol biosynthetic pathway, which plays an important role in regulating cholesterol biosynthesis. In the present study, rat MDD was cloned and purified to apparent homogeneity. Two fluorinated MDD substrate analogs, P′-geranyl 2-fluoromevalonate 5-diphosphate (4) and 2-fluoromevalonate 5-diphosphate (6), were synthesized, and both were found to be irreversible inhibitors of rat MDD. These two inhibitors were characterized, and mechanisms of the inactivation process were proposed. Kinetic studies indicate both analogs only bind into mevalonate binding-site of MDD. Compound 4 shows competitive inhibition on mevalonate kinase (MVK), and its IC 50 value was determined to be comparable with that of geranyl diphosphate. Further kinetic studies indicate compound 4 only bind into ATP binding-site of MVK. These studies provide an example for a single inhibitor to carry out sequential blocking of two enzymes in cholesterol biosynthesis, which may provide useful information for drug discovery for the purpose of treating cardiovascular disease and cancer or for pest control.